Prevalence of back pain in employees of a German chemical company: results of a large cross-sectional study - Matthias Claus; Michael Schuster; Stefan Webendörfer; David A. Groneberg; Jacqueline Jähner; Daniel Schiffmann (Journal of Occupational Medicine and Toxicology, 2019)
Abstract Background With the current study, we aimed to determine the prevalence of back pain in employees of a German chemical company. We put a specific focus on disabling back pain and its association with sociodemographic, lifestyle- and work-related characteristics. Methods We used cross-sectional data, surveyed in health check-ups between 2011 and 2014 in Ludwigshafen am Rhein (Germany). A blood sample, physical examination and anamnesis by an occupational health physician as well as a written questionnaire were part of the check-up. A modified version of the Standardised Nordic Musculoskeletal Questionnaire was utilized to survey the back-pain specific information. Disabling back pain was defined as presence of any back pain in the past 12 months which prevented employees from carrying out their usual working tasks. We used multinomial logistic regression analysis to assess the association between (categorical) duration of disabling back pain and sociodemographic, lifestyle-, and work-related characteristics. Results Overall, 17,351 employees participated in the health check-up, information on 16,792 persons could be used for analyses. Participants were on average 43.7 (SD: 9.7) years old and mainly male (79.1%). Lifetime-, 12-months-, and 7-days-prevalence of any type and duration of back pain were 72.5, 66.1, and 27.1% respectively. About one third (33.5%) had suffered from an episode of disabling back pain, 16.7% 1–7 days, 10.3% 8–30 days, and 6.5% more than 30 days. Multinomial regression analysis yielded that 8–30 days or more than 30 days of disabling back pain (relative to 0 days) were more likely with older age, female gender, being married, former or current smoking, lower occupational status, higher work-related stress score, history of a spinal injury, and diagnosed dorsopathy. Conclusions There is a great need for action regarding multifaceted preventive measures and early interventions, especially for manual workers, older employees and women, where occupational medicine can play a decisive role.